Genetic Regulation of Symbiosis Island Transfer in Mesorhizobium loti - Ramsay, Joshua; Ronson, C. (2015)
The Mesorhizobium loti symbiosis island (ICEMlSymR7A) is a 500-kb mobile integrative and conjugative element (ICE) that converts non-symbiotic mesorhizobia into strains capable of forming a symbiosis with Lotus corniculatus. ICEMlSymR7A chromosomal excision and conjugative transfer is stimulated by the quorum-sensing regulator TraR. Quorum sensing and ICEMlSymR7A excision/transfer is inhibited in the majority of the M. loti population by QseM, a recently identified protein antiactivator of TraR. QseM expression is in turn regulated by the DNA-binding protein QseC, which binds and represses the qseM promoter in a concentration-dependent manner. We propose that this complex regulation forms a molecular switch allowing activation of quorum sensing, excision and transfer in a small proportion of cells in the population, rather than the population-wide activation typical of many quorum-sensing systems.